1989
DOI: 10.1111/j.1365-2389.1989.tb01254.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lime on adsorption and desorption of phosphate in five Colombian soils

Abstract: The effects of lime (applied in the field) on the amounts of total and isotopically-exchangeable phosphate adsorbed from solutions were measured in five soils. The total amount of phosphate adsorbed without lime was in the range 200 to 1700 pg P per g of soil at 0.05 pg P cm-3 of solution. Lime diminished the amount of phosphate adsorbed at all concentrations of solution in an oxisol and a dystropept; in an ultisol and another dystropept, lime tended to increase sorption at small concentrations and diminish it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Rowell [50] reported that P in the MPR is available in the first season after application but remains over long periods of time hence their residual effects. This has also been reported by other workers [76,77,78,79,80]. In terms of improving the soil P status, rock phosphates have both immediate and residual effects [1].…”
Section: Relative Agronomic Efficiency (Rae) Of Minjingu Phosphate Rocksupporting
confidence: 78%
“…Rowell [50] reported that P in the MPR is available in the first season after application but remains over long periods of time hence their residual effects. This has also been reported by other workers [76,77,78,79,80]. In terms of improving the soil P status, rock phosphates have both immediate and residual effects [1].…”
Section: Relative Agronomic Efficiency (Rae) Of Minjingu Phosphate Rocksupporting
confidence: 78%
“…Air-dried soil (0-15 cm) had a pH of 5.3 (1:2.5 soil:water); organic carbon 105 g kg -1 ; exchangeable calcium 3.05 cmol c kg -1 , magnesium 0.96 cmol c kg -1 , potassium 0.28 cmol c kg -1 ; bicarbonate-EDTA extractable phosphorus 1.27 mg kg -1 . P sorption is very high; based on sorption isotherms, 1,000 mg P kg -1 of soil was required to raise soil solution P to 0.2 mg l -1 for 0-15 cm soil (Le Mare and Leon 1989).…”
Section: Andisol In Colombiamentioning
confidence: 99%
“…Thus, adsorption and desorption of cations and anions is influenced by soil pH (McBride, 1989). The change of a soil pH by the addition of a basic soil amendment (lime) or by use of an acidifying fertilizer (ammonium) or any management practice that changes the soil pH effectively changes the cation exchange capacity (CEC) and anion exchange capacity (AEC) of certain soils (Wright et al, 1989; Le Mare and Leon, 1989). Some colloids have a point of zero charge (PZC) (Wada, 1989).…”
Section: Properties Of Andisols That Influence Soil Use and Managemenmentioning
confidence: 99%